2018
DOI: 10.1021/acschemneuro.8b00310
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-like Structures Formed by Single Amino Acid Self-Assemblies of Cysteine and Methionine

Abstract: We report for the very first time the discovery of amyloid-like self-assemblies formed by the nonaromatic single amino acids cysteine (Cys) and methionine (Met) under neutral aqueous conditions. The structure formation was assessed and characterized by various microscopic and spectroscopic techniques such as optical microscopy, phase contrast microscopy, scanning electron microscopy, and transmission electron microscopy. The mechanism of self-assembly and the role of hydrogen bonding and thiol interactions of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
138
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(138 citation statements)
references
References 57 publications
0
138
0
Order By: Relevance
“…Chronic hMet and its oxidative product, Met sulfoxide, induces cellular oxidative stress [ 7 , 8 ] in various organs and also contributes to the brain pathology [ 9 , 10 , 11 ]. Moreover, Met can undergo spontaneous self-assembly to form amyloidogenic aggregates [ 12 ], and an increased Met oxidation in the apolipoprotein A-I could nucleate amyloidogenesis, which eventually leads to the aggregation into amyloid fibrils [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hMet and its oxidative product, Met sulfoxide, induces cellular oxidative stress [ 7 , 8 ] in various organs and also contributes to the brain pathology [ 9 , 10 , 11 ]. Moreover, Met can undergo spontaneous self-assembly to form amyloidogenic aggregates [ 12 ], and an increased Met oxidation in the apolipoprotein A-I could nucleate amyloidogenesis, which eventually leads to the aggregation into amyloid fibrils [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insoluble brillar polypeptide structures appear as a result of a misfolding process in numerous proteins or peptides and accompany the amyloid aggregation process. [1][2][3][4][5][6] The most spectacular structures of this type are linked to the development of fatal neurodegenerative disorders such as Alzheimer's disease, 7,8 Icelandic type amyloidosis 9,10 or Creutzfeldt-Jakob disease. 11,12 The latter belongs to the group of diseases called transmissible spongiform encephalopathies (TSE) in which a misfolding of human prion protein (PrP) is responsible for the formation of brillar aggregates in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…10,[38][39][40][41][42] Recently, we reported selfassembled structure formation of cysteine and methionine and its amyloid like characteristic. 3 In other study our group has also reported the self-assembled structure formed by proline, hydroxyproline 35 and lysine.HCl. 43 Further in our another research we study the self-assembly of acyl thiourea based organic molecules and its application for the sequential detection of copper and lactic acid and it has been used for the cell imaging applications 43 Hence, from our previous studies we were motivated to synthesizea modified version of single amino acid which can be effectively used forvarious biomedical applications.…”
Section: Introductionmentioning
confidence: 86%
“…Recently, our group reported the self-assembly of single amino acid cysteine and methionine 3 Wangoo et al also reported the self-assembly of various single amino acids and reported potential application of these supramolecular building blocks in material science, 29 In other study Fmoc variant cysteine is used as anticancer drug delivery agent, 30 In another report self-assembly of fluorenyl-methoxy-carbonyl-β,β-diphenyl-Ala-OH (Fmoc-Dip-Ala) to opel gemstone like morphologies is reported, 31 Bai et al designed different Fmoc-dipeptide and examined its catalytic role as thermolysin. 32 In another study mechanical properties of Fmocdiphenylalanine were studied 33 and also the self-assembly of Fmoc-peptides was used for the preparation of nanostructures and hydrogels, 34 Our group has been interested in assessing the self-assembling properties of single amino acids, 3,35 peptides, [36][37][38] and heterocyclic compounds. 10,[38][39][40][41][42] Recently, we reported selfassembled structure formation of cysteine and methionine and its amyloid like characteristic.…”
Section: Introductionmentioning
confidence: 99%